Imagining catholicism on facebook: A study of catholic online masses as a ceremony of an imagined community - Yatco, Christian Bryan Songcuan (Animo Repository, 2023)
Imagined Communities (IC) is a theory that may provide a means of understanding the construction of a community by way of the imagination of its members. Through communicative platforms, a collective imagination can be rendered visible in the minds of the individuals within the community. In this study, the author hypothesizes that such an imagination can be sustained through a social media platform like Facebook, by investigating how the digital platform contributes to the construction of a community among Filipino Catholics who are actively attending the livestream masses on Facebook Live of the Sambuhay TV Mass. While Catholicism has remained for five hundred years as a prominent religion in the Philippines, the Church’s utilization of the mass media has proven instrumental in its continuity. However, little research has been devoted to the role of social media in the Church’s propagation. Its ubiquity in today’s social media platforms enables the Filipino Catholics to connect to other members of their community online through the mediatized ceremony of the Holy Mass. This study will discuss how IC entails a process of mediatization that engages Filipino Catholics through the presentation of the Holy Mass on the Facebook Live of Society of Saint Paul Philippines’ Sambuhay TV Mass. Facebook, as a new technical means, provides an avenue for the Filipino Catholics to construct and sustain their IC by sharing a common language among the other members; the availability of kinship; and the simultaneity of the imagination. The study used the visual elicitation method in qualitative research to examine the construction of an IC and to gather and interpret the data. The result of this study will be beneficial to the Filipino Catholics and also to the Catholic Church to understand the framework of their community that is mediatized through Facebook.